Faecal Carriage of Carbapenem-Resistant Acinetobacter baumannii: Comparison to Clinical Isolates from the Same Period (2017–2019) - Bence Balázs; Zoltán Tóth; József Bálint Nagy; László Majoros; Ákos Tóth; Gábor Kardos (Pathogens, 2022)
Increasing prevalence of A. baumannii was found in the faecal samples of inpatients without infection caused by A. baumannii (0.15%; 55/7806). The aim of the study was to determine whether there is a relationship between the clinical strains and the increased faecal occurrence. Characteristics of faecal and clinical isolates were compared between 2017 and 2019, and the direction of causality was assessed by Granger causality tests. In the case of the antibiotic resistance, faecal carriage of carbapenem-resistant Acinetobacter baumannii (CRAb) was Granger-caused by prevalence of CRAb in inpatients (F = 15.84, p < 0.001), but inpatient prevalence was not Granger-caused by CRAb faecal carriage (F = 0.03, p = 0.855). Whole genomes of 16 faecal isolates were sequenced by Illumina MiSeq; cgMLST types were determined. In faecal isolates, the occurrence of carbapenem resistance was lower than among the clinical isolates from the same period; only blaOXA-72 harbouring ST636 and ST492 were detected, and the blaOXA-23 harbouring ST2 and ST49 strains previously dominant in clinical isolates were absent. Carriage of blaOXA-72 was linked to pMAL-1-like and pA105-2-like plasmids in ST636 and ST492 isolates, respectively, both in clinical and faecal isolates. The new ST636 and ST492 strains may colonise the gut microbiota of the patients, which thus may play a role as a reservoir.